Kualitas Pelayanan Pengurusan Suart Izin Usaha Perdagangan (SIUP) Pada Kantor Badan Pelayanan Perizinan Terpadu Kota Palu - Sussanti Sussanti (Jurnal ADMINISTRATOR, 2023)
This study aims to find out how the Quality of Service for the Management of Trade Business Permits (SIUP) at the Integrated Licensing Service Agency of Palu City. This type of data is done through observation, interviews, and documentation. Informant withdrawal technique uses purposive, data analysis used is the Miles and Huberman model, namely data reduction and conclusion drawing. The theory used is Zeithaml, Parasurumana and Berry which consists of 5 (five) dimensions, namely: Tangibels, Reliability, Responsiveness, Assurance and Empathy. Based on the results of the research carried out, that the quality of service for the Management of Trading Business Permits is not optimal. Dimensions of tangibles, inadequate facilities and infrastructure such as the lack of space for waiting rooms and chairs provided. The ability of officers/employees to use assistive devices is very good. Responsiveness, the response of officers/employees who received the applicant's complaints was very good, but the speed in completing the issuance of permits was not maximized. Assurance, the guarantee given by the officer/employee to the applicant is not on time, but the permit fee charged is in accordance with applicable regulations. Empathy, namely the service provided is not discriminatory and the officers/employees always provide service in a polite and friendly manner. Thus, from the five dimensions of service quality above, there are still some things that need to be addressed, so that the quality of service provided is more leverage